A new species of Leotichius Distant (Hemiptera: Heteroptera: Leptopodidae) from Cambodia - Jung, Sunghoon; Duwal, Ram Keshari; Lee, Seunghwan (Zootaxa, 2013)
One new species, Leotichius schuhi Jung sp. nov., that shared habitat with the larvae of xeric adapted ant-lions (Neuroptera), is described from northern Cambodia. Diagnosis, description and biological notes of the new species are presented.